2010
DOI: 10.1007/s11627-010-9278-7
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation as yield enhancement strategy for glycyrrhizin production by cell cultures of Abrus precatorius Linn.

Abstract: Glycyrrhizin is an important phytoconstituent of licorice which is widely used in the pharmaceutical and food industry. As the roots and leaves of Abrus precatorius also contain glycyrrhizin, it can be used as an alternative source of glycyrrhizin. In spite of extensive research work undertaken with cultures of Glycyrrhiza glabra, the glycyrrhizin production remains elusive. Successful production of glycyrrhizin in cell cultures of A. precatorius is being reported for the first time in our study. Cell cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 48 publications
0
20
1
Order By: Relevance
“…No glycyrrhizin was detected in A. precatorius spent culture medium. Our previous report (Karwasara et al 2010) showed that the fungal elicitors prepared from the A. niger and R. stolonifer have higher influence in stimulating glycyrrhizin accumulation (5.2 fold higher) in A. precatorius cell culture than the potency of OT demonstrated in the present study but still the significant effect of OT cannot be ruled out concerning the production of biomass and glycyrrhizin. The results suggest that OT is a potent growth stimulator as well as elicitor for enhanced production of glycyrrhizin.…”
Section: Elicitationcontrasting
confidence: 74%
See 4 more Smart Citations
“…No glycyrrhizin was detected in A. precatorius spent culture medium. Our previous report (Karwasara et al 2010) showed that the fungal elicitors prepared from the A. niger and R. stolonifer have higher influence in stimulating glycyrrhizin accumulation (5.2 fold higher) in A. precatorius cell culture than the potency of OT demonstrated in the present study but still the significant effect of OT cannot be ruled out concerning the production of biomass and glycyrrhizin. The results suggest that OT is a potent growth stimulator as well as elicitor for enhanced production of glycyrrhizin.…”
Section: Elicitationcontrasting
confidence: 74%
“…Seeds of A. precatorius, were sterilized and germinated by following the protocol described in our previous publication (Karwasara et al 2010). …”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations